Scientific Workflow-Based Synthesis of Optimal Microgrid Configurations - Olga Edeleva; Alexei Edelev; Mikhail Voskoboinikov; Alexander Feoktistov (Energies)
Nowadays, multi-energy systems play an important role in satisfying the ever-increasing demand for different energy resources. At the same time, the sustainable development of such systems is usually based on the structural and parametric optimization (synthesis) of their infrastructures. There is a large spectrum of specialized optimization tools for the study of single energy systems. At the same time, the problem of modeling the interaction between single energy systems remains challenging. Therefore, it is imperative to develop an efficient experimental environment to effectively implement the synthesis of optimal configurations of multi-energy systems. Microgrids are a special case of multi-energy systems. They provide a higher level of energy supply compared to the main grids and enhance their reliability and resilience. In this context, we propose a framework and subject-oriented environment for the synthesis of optimal microgrid configurations in a reasonable time considering the available computational resources. The basis of the environment is a service-oriented application. The modeling and optimization of the studied systems is performed by means of scientific workflows. Our results complement and develop known approaches to automate the modeling of multi-energy systems using their typical models and specially selected optimization algorithms corresponding to these models. We have successfully tested our approach for the synthesis of optimal microgrid configurations on the case study of a specific microgrid providing heat and electricity to a small settlement.